2011
DOI: 10.1007/s00421-011-2225-4
|View full text |Cite
|
Sign up to set email alerts
|

l-Arginine but not l-glutamine likely increases exogenous carbohydrate oxidation during endurance exercise

Abstract: The addition of L-arginine or L-glutamine to glucose-electrolyte solutions can increase intestinal water, glucose, and sodium absorption in rats and humans. We evaluated the utility of L-arginine and L-glutamine in energy-rehydration beverages through assessment of exogenous glucose oxidation and perceptions of exertion and gastrointestinal distress during endurance exercise. Eight cyclists rode 150 min at 50% of peak power on four occasions while ingesting solutions at a rate of 150 mL 15 min(-1) that contain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 50 publications
(69 reference statements)
1
11
0
Order By: Relevance
“…Our finding of no change to the rate of exogenous carbohydrate oxidation with the co-ingestion of either a whey or casein hydrolysate agrees with the previous finding when a whole milk protein concentrate is co-ingested with carbohydrate [37]. However, co-ingestion of the single amino acid arginine increases the rate of exogenous carbohydrate oxidation supposedly via an increase in nitric oxide and intestinal vasodilation [34]. Arginine, although present in both the whey and casein hydrolysates and supplied at a similar rate (~0.5 g/h) as in the study of Rowlands et al [34], may have been absorbed as di and tri-peptides [21,26] and not individual amino acids and thereby may limit the nitric oxide stimulating potential.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…Our finding of no change to the rate of exogenous carbohydrate oxidation with the co-ingestion of either a whey or casein hydrolysate agrees with the previous finding when a whole milk protein concentrate is co-ingested with carbohydrate [37]. However, co-ingestion of the single amino acid arginine increases the rate of exogenous carbohydrate oxidation supposedly via an increase in nitric oxide and intestinal vasodilation [34]. Arginine, although present in both the whey and casein hydrolysates and supplied at a similar rate (~0.5 g/h) as in the study of Rowlands et al [34], may have been absorbed as di and tri-peptides [21,26] and not individual amino acids and thereby may limit the nitric oxide stimulating potential.…”
supporting
confidence: 91%
“…The PL trial served mainly to provide correction for background enrichment and comparison of outcome variables with the PL trial is only done when it aids in supporting identified changes between the 3 energy drink trials. To allow comparison with a large proportion of the recently published studies in this field, data were analysed using probabilistic magnitude-based inferential analysis, which has been recommended as the way forward [1,12] and has been described previously [2,28,29,[33][34][35][36][37]44] for analysing the physiological magnitude of effect. Inferential analysis was performed using published spreadsheets [9,11].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, HR was possibly lower with ALA compared with PLA at both 20-and 120-min of the constant-load phase. Perhaps this precipitated from the intestinal cotransport mechanism described above; ALA may have facilitated sodium and water absorption across the gut (Rowlands et al, 2012;Van Loon et al, 1996;Wapnir et al, 1988) thereby preserving plasma volume (Hall et al, 2013) and reducing HR. The importance of this response is questionable though considering that this did not elicit a lower RPE than PLA nor did the lower HR persist into the TT.…”
Section: Discussionmentioning
confidence: 97%
“…Neutral amino acids are cotransported with sodium across the intestines via glucose independent transporters (Coëffier et al, 2005). Additional sodium absorption across the gut may increase transport of water via solvent drag (Rowlands et al, 2012;Van Loon et al, 1996;Wapnir et al, 1988), which could tenably preserve plasma volume (Hall et al, 2013) and as a result minimize cardiovascular drift (HR) and perceptual strain (Casa et al, 2010). Our data (RPE and HR) suggest that PRO alone does not systematically alter these parameters.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation